LITERATURE REVIEW. MODERN CONCEPTS OF THE DEVELOPMENT OF MULTIPLE MYELOMA - Mahamadalieva G. Z.; Karimov Kh. Ya. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Multiple myeloma is - an incurable disease, characterized by significant morbidity and mortality [5, 8, 20]. Among the risk factors for the development of multiple myeloma, as well as other oncohematological diseases, hereditary predisposition, genetic factors, immune system status, as well as exposure to ionizing radiation, toxic substances, unfavorable environmental factors, and prolonged exposure to psycho-emotional stress are of particular importance. [1, 2, 6,9]. Currently, there is no convincing evidence that any of the listed factors play a decisive role in the development of multiple myeloma (MM) [5, 8, 20]. Experimental studies show that the influence of one factor is insufficient for tumor progression. To manifest an oncological phenotype, the simultaneous influence of several factors is required. Modern scientific publications attest to the heterogeneous nature of MM and emphasize the importance of genetic factors in its etiology. [1, 3, 7, 10]. Polymorphisms of the genes of inflammatory factors may be involved in the progression of MM due to the imbalance of pro-and anti-inflammatory cytokines profile. [9, 10, 24, 30]. The family of interleukins (IL), which participate in the immune response and inflammatory processes of MM, consists of a group of lymphatic factors with many biological activities.